2018
DOI: 10.1159/000485470
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Sensor Technology Can Capture Changes in Dynamic Balance Control during the Y Balance Test

Abstract: Introduction: The Y Balance Test (YBT) is one of the most commonly utilised clinical dynamic balance assessments. Research has demonstrated the utility of the YBT in identifying balance deficits in individuals following lower limb injury. However, quantifying dynamic balance based on reach distances alone fails to provide potentially important information related to the quality of movement control and choice of movement strategy during the reaching action. The addition of an inertial sensor to capture more det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…However, the traditional clinical scoring method does not allow for the objective quantification of information related to an individual's balance 'stability' or 'strategy'. Recent research has resulted in the development of an inertial sensor quantified YBT (QYBT), demonstrating that it can provide a reliable measure of performance [17], is more sensitive to change than the traditional scoring method [18,19] and can identify deficits in performance that increase an athletes risk of concussion [20]. To date, despite a call for research, there have been no prospective investigations conducted to determine the capability of an inertial sensor based assessment to quantify motor function following 'clinical recovery' from concussion [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional clinical scoring method does not allow for the objective quantification of information related to an individual's balance 'stability' or 'strategy'. Recent research has resulted in the development of an inertial sensor quantified YBT (QYBT), demonstrating that it can provide a reliable measure of performance [17], is more sensitive to change than the traditional scoring method [18,19] and can identify deficits in performance that increase an athletes risk of concussion [20]. To date, despite a call for research, there have been no prospective investigations conducted to determine the capability of an inertial sensor based assessment to quantify motor function following 'clinical recovery' from concussion [7].…”
Section: Introductionmentioning
confidence: 99%
“…The intra-session reliability and inter-session reliability of the data acquisition parameters and sensor mounting location have been previously published. 14,15 Furthermore, recent research has demonstrated the discriminant validity of the inertial sensorbased approach, 13,20 as well as highlighted the capacity of the assessment to capture balance deficits with are associated with an increased risk of concussion in rugby union players. 15 It has previously been reported that investigating the discriminant capabilities of inertial sensor-based variables may be the most appropriate method for validation of these tools.…”
Section: Dynamic Balance Testingmentioning
confidence: 99%
“…5 For example, recent research has shown that a single lumbar-worn inertial sensor can provide a valid and reliable measure of dynamic movement control during the YBT. 13,14 Early investigations of this approach within the clinical context have shown that it may have value in identifying athletes at a three-times higher relative risk of sustaining a concussion, 15 as well as identifying post-concussion deficits. 6 Therefore, the inertial sensor instrumentation of the YBT may allow for the accessible and objective quantification of sensorimotor performance outside of the laboratory environment, helping to identify individuals who may be at an increased risk of future injury.…”
mentioning
confidence: 99%
“…Twelve studies assessed discriminant validity in healthy cohorts, assessing the ability of inertial sensor systems to discriminate between known stance, visual, hearing, fatigue or taping conditions [25,28,32,41,[43][44][45][46][47][48][49][50].…”
Section: Discriminant Validity -Healthy Populationmentioning
confidence: 99%
“…A single prospective cohort study investigated the association of inertial sensor-based PC assessment scores with sports related injuries in a cohort of collegiate American football players, reporting that players with poorer PC were at a 5.19 times greater-odds of sustaining a sports related injury [61]. Table here 3.6 MEASUREMENT RELIABILITY Thirteen of the included studies were identified as assessing measurement reliability [16,27,28,33,40,41,45,47,58,[62][63][64][65]. Eleven of these studies investigated intra-session test retest reliability, demonstrating reliability ranging from poor to excellent (ICC = 0.03 to 0.97) [16,27,33,40,41,45,47,58,[63][64][65], while five studies reported poor to excellent (ICC = 0.02 to 0.95) inter-session reliability [16,28,[62][63][64].…”
Section: Predictive Validity -Sports Medicine Populationsmentioning
confidence: 99%